If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(1 + 5x) = 3(-4x + -2) (1 * -3 + 5x * -3) = 3(-4x + -2) (-3 + -15x) = 3(-4x + -2) Reorder the terms: -3 + -15x = 3(-2 + -4x) -3 + -15x = (-2 * 3 + -4x * 3) -3 + -15x = (-6 + -12x) Solving -3 + -15x = -6 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. -3 + -15x + 12x = -6 + -12x + 12x Combine like terms: -15x + 12x = -3x -3 + -3x = -6 + -12x + 12x Combine like terms: -12x + 12x = 0 -3 + -3x = -6 + 0 -3 + -3x = -6 Add '3' to each side of the equation. -3 + 3 + -3x = -6 + 3 Combine like terms: -3 + 3 = 0 0 + -3x = -6 + 3 -3x = -6 + 3 Combine like terms: -6 + 3 = -3 -3x = -3 Divide each side by '-3'. x = 1 Simplifying x = 1
| 13+2(1-u)=8u-5(u+7) | | 14X=6X+16 | | 12x+48=5x-117 | | (6x-7y)(6x-7y)= | | 5x+8=-8 | | 5+(3y+3)=-(3-4)+8 | | 7m+8=3m-16 | | 6x^2=27x+15 | | 4(a+2)=2(-2+a)-4 | | 2p+18=p-8 | | 27-5X=-3 | | 7+5p+6P=7p-1+5p+16 | | 3(x+9y)=3(x+9y) | | -4(6x-1)-3(5x-6)=12x+5 | | 10n-22=8n-14 | | 30x^3+25x^2+5x=0 | | 5x+9y=164x-6y=26 | | 4x+3(6x-5)= | | 0.33333y=-7 | | (8a+9)(8a-9)= | | f(2)=7-3(2)(2) | | 9x+15=-2x-18 | | f(3)=7-3(2)(2) | | 9n+14=11n | | 4x-1=2x-7isx | | 11(3w-2)-14w=2w+3 | | 5x+9y=16 | | -8-8(-z+6)=7(-6z-6)-8 | | 20x-16=-17 | | -2x+-6=-2x+-2-4 | | 6-2(2w-1)=9w-2(9+w) | | 24=-6+3y |